Social and clinical profile of children and adolescents with type 1 diabetes mellitus - Cavalcante, Maria Eduarda Pires Lima (2023)
Objective: to identify the social and clinical profile of children and adolescents with type 1 diabetes mellitus. Method: quantitative, cross-sectional and descriptive research, developed with 81 guardians of children and adolescents with type 1 diabetes mellitus between March and September/2021, in two reference centers in Paraiba. The descriptive analysis was performed using the Statistical Package for the Social Science software, version 18. Results: predominantly, the companions of the children and adolescents were the mothers themselves, 90.1%, and about 40% lived with family income lower than a minimum wage. Among the children and adolescents, 54% had high glycated hemoglobin values, even though they were undergoing treatment; 65.4% indicated ignorance of the correct form of insulin storage, and 77.6% had lipohypertrophy. Conclusion: socioeconomic vulnerability and ineffective clinical management of type 1 diabetes mellitus in children and adolescents were predominant.